Optimalisasi Pemberdayaan Masyarakat Berbasis Masjid - Ade Iwan Ridwanullah; Dedi Herdiana (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2018)
The mosque has a very strategic function in the Islamic community both as a place of worship and a media center for fostering people in a holistic manner. This paper describes the optimization of mosque functions as a center of community empowerment activities and the factors that influence it. The research method uses qualitative descriptive methods through interviews, field notes, and documentation. The place of research is at-Taqwa Cirebon Grand Mosque. The results showed that the At-Taqwa Cirebon Grand Mosque represented a mosque that was able to revive the spirit of the community empowerment movement in the spiritual, economic, educational, social, and cultural arts development fields. The success of mosque-based community empowerment activities at At-Taqwa Grand Mosque is supported by adequate human resources reflected in the ideal organizational structure of the mosque's board of directors and supported by effective communication skills of the da'is. This study recommends the importance of mosque management professionalism and the importance of managing effective communication with both congregations and other stakeholders. This study enriches the study of the development of Islamic societies, especially in mosque-based community empowerment.Masjid memiliki fungsi yang sangat strategis dalam masyarakat Islam baik sebagai tempat ibadah maupun pusat media pembinaan umat secara holistik. Tulisan ini menggambarkan optimalisasi fungsi masjid sebagai pusat kegiatan pemberdayaan masyarakat dan faktor-faktor yang mempengaruhinya di dalamnya. Metode penelitian menggunakan metode deskriptif kualitatif melalui wawancara, catatan lapangan, dan dokumentasi. Tempat penelitian adalah Masjid Raya at-Taqwa Cirebon. Hasil penelitian menunjukkan bahwa Masjid Raya At- Taqwa Cirebon merepresentasikan masjid yang mampu menghidupkan semangat gerakan pemberdayaan masyarakat dalam bidang spiritual keagamaan, ekonomi, pendidikan, sosial kemasyarakatan, dan pengembangan seni budaya. Keberhasilan kegiatan pemberdayaan masyarakat berbasis masjid di Masjid raya at-Taqwa didukung oleh sumber daya manusia yang memadai yang tergambar dalam struktur organisasi dewan pengurus masjid yang ideal serta ditunjang kemampuan komunikasi efektif dari para da’i. Penelitian ini merekomendasikan pentingnya profesionalisme pengelolaan masjid dan pentingnya mengelola komunikasi yang efektif baik dengan jemaah maupun stakeholders yang lain. Penelitian ini memperkaya kajian tentang pengembangan masyarakat Islam khususnya dalam pemberdayaan masyarakat berbasis masjid.